DYNLT3 overexpression induces apoptosis and inhibits cell growth and migration via inhibition of the Wnt pathway and EMT in cervical cancer - Zhang, Jianan; Shen, Qi; Xia, Lu; Zhu, Xueqiong; Zhu, Xuejie (Frontiers in Oncology, 2022)
The role of the dynein light chain Tctex-type 3 (DYNLT3) protein in the biological behavior of cervical cancer and its relative molecular mechanisms were investigated. Immunohistochemical staining was used to detect DYNLT3 protein expression in cervical cancer tissues. Cell proliferation and apoptosis rates and invasiveness and migratory capacities were determined by CCK-8 assays, BrdU staining assays and colony formation assays, fluorescence activated cell sorting (FACS), wound healing assays, and Transwell invasion assays of cervical cancer cells after DYNLT3 modulation. The expression levels of Wnt signaling pathway- and EMT-related proteins were examined by Western blotting. Furthermore, the effects of DYNLT3 on the tumorigenicity and metastasis of cervical cancer in nude mice were analyzed by performing immunohistochemistry, and we found that the expression level of the DYNLT3 protein was higher in human normal cervical tissues than in cervical cancer tissues. Overexpression of DYNLT3 obviously attenuated the proliferation, migration and invasion of CaSki and SiHa cells, and promoted cell apoptosis. Upregulation of DYNLT3 expression markedly decreased the expression of Wnt signaling pathway-related proteins (Dvl2, Dvl3, p-LRP6, Wnt3a, Wnt5a/b, Naked1, Naked2, β-catenin and C-Myc) and EMT-related proteins (N-cadherin, SOX2, OCT4, vimentin and Snail), and increased the expression of E-cadherin and Axin1. However, the opposite results were observed after down-regulation of DYNLT3 expression. Up-regulation of DYNLT3 expression significantly inhibited tumor growth in a nude mouse model, while downregulation of DYNLT3 showed the opposite results. In addition, the major metastatic site of cervical cancer cells in mice was the lung, and downregulation of DYNLT3 expression increased cancer metastasis in vivo. DYNLT3 exerted inhibitory effects on cervical cancer by inhibiting cell proliferation, migration and invasion, promoting cell apoptosis in vitro, and inhibiting tumor growth and metastasis in vivo, possibly by suppressing the Wnt signaling pathway and the EMT.